The Effect of Financial Literacy and Financial Technology on Msme Business Performance in Sidoarjo - Fatmawati, Ananda Azkia; Hariyati, Hariyati (CV. Green Publisher Indonesia, 2025)
Due to their substantial contributions to employment and local productivity, MSMEs are essential to Indonesia's economic stability. MSMEs in areas like Sidoarjo, however, continue to struggle with funding, marketing, and operational effectiveness. The purpose of this study is to examine how financial technology and financial literacy affect MSMEs' operations in Sidoarjo's food and beverage industry. Questionnaires were used to gather quantitative data from 115 respondents who were chosen using purposive sampling. The associations between the variables were investigated using multiple linear regression analysis. The findings demonstrate that technology and financial literacy have a favorable and significant impact on the success of MSME businesses. Financial literacy enhances entrepreneurs’ capabilities in managing cash flow, budgeting, debt, and investments. Meanwhile, fintech improves operational efficiency and financial access through digital platforms such as QRIS payments and online lending. These findings align with the resource-based view and financial behavior theories, emphasizing the strategic value of internal resources and the psychological dimensions of decision-making. The study highlights the need for integrative strategies combining education and technology adoption to elevate MSME competitiveness and sustainability. Future research could focus on longitudinal and comparative regional studies to better understand the dynamics and barriers of fintech and financial literacy in MSME development.